Sesquicentenario de la anestesia : un aporte de la odontología a la humanidad (1994)
ABSTRACT: In December 11, 1994 we commemorate the 150 the anniversary of the discovery of anesthesia. Four gentlemen, in the 19th century, disputed among themselves the honor of this discovery: Charles Jackson (Chemist), Crawford Long (Physician) William Morton (dentist) and Horace Wells (dentist). In 1800, Crawford Long did some experiments with Nitrous Oxide and postulated that it could abolish pain even in mayor surgeries; despite of this he didn’t continue his experiments. In 1844, Horace Wells tried Nitrous Oxide as an anesthetic and continued experimenting with it for several years. Later on, he communicated his discovery in Boston, without success, and in Paris, where he was rewarded with the title of Doctor in Medicine. In 1846, Charles Jackson and William Morton experimented with ether, made public its success as an anesthetic, and patented it. Morton was accepted worldwide, as the discover of anesthesia from 1848 until 1863. In 1864 the American Dental Association, by resolution, recognized Horace Wells as the real discoverer, but it was a little too late since Wells had already died. In 1870, the American Medical Association also accepted Horace Wells as the discover of anesthesia.